IMPACT OF MODAL CHOICE IN ENERGY CONSUMPTION AND CARBON DIOXIDE EMISSIONS: ANALYSIS OF BRAZILIAN BIOETHANOL SUPPLY CHAIN - Lopes, Juliana Monteiro; Leal Junior, Ilton Curty; Guimarães, Vanessa de Almeida (Brazilian Journal of Operations & Production Management, 2016)
Currently, concerns with sustainable development lead organizations to improve their production processes in order to reduce greenhouse gases emission and energy consumption. Since the bioethanol supply chain is a CO2 emitter and depends on several energy sources, it becomes important to analyze how to improve this chain regarding environmental issues. Thus, this paper presents a comparative study of scenarios with bioethanol supply chain configurations which use different modal alternatives and renewable energy in all its mid-stages. The analysis was based on LCA (life cycle analysis) concepts and in a partial application of LCI (life cycle inventory), so that we can identify which of these scenarios is most appropriate in terms of lower total energy consumption, greater share of renewable energy use and lower CO2 emissions. Based on concepts found in the bibliographic research, the methodology used and the data collected from documental research, this paper analyzes the supply chain that begins with sugarcane plantation and bioethanol production in the south central region of Brazil with destination to export. Based on the results, we concluded that it is possible to improve the performance of the supply chain in environmental terms with a combination of renewable energy sources and modes of transport that are more suitable to the product studied.